β-caryophyllene attenuates oxidative stress and hepatocellular mitochondrial dysfunction in type-2 diabetic rats induced with high fat and fructose diets - Mani, Vadivel; Dash, Ipsita; Chandrashekar, Sangeeta; Natarajan, Muninathan (International Journal of Health Sciences, 2024)
Objective: Hyperglycemia, hyperlipidemia, and systemic resistance to insulin are typical manifestations of type 2 diabetes mellitus. One of the main pathophysiological alterations in insulin-sensitive organs is mitochondrial malfunction associated with oxidative stress and diminished fuel utilization. β-Caryophyllene (BCP) has qualities that are anti-inflammatory, anti-tumor, antioxidant, hypolipidemic, and hypoglycemic. In this work, rats suffering from type 2 diabetes were given a diet high in fat and sugar with the aim of examining the ameliorative effects of BCP on oxidative stress-mediated hepatic mitochondrial dysfunction. Methods: The diabetic condition was experimentally induced by feeding rats a highcalorie diet. The rats were then administered the recommended doses of BCP and metformin (MET) once every day for 30 days at 200 mg and 50 mg concentrations per kg of body weight, respectively, to prove the hypothesis of the study that BCP ameliorates mitochondrial dysfunction induced by oxidative stress in diabetic rats. Mitochondrial dysfunction can be identified by indicators such as oxidative stress, cardiolipin dienes, membrane phospholipid concentration, and mitochondrial enzymes. Results: The mitochondria in the liver of rats with diabetes exhibit elevated redox imbalance-related parameters and malfunctioning mitochondria with peroxided cardiolipin, while their amounts of glutathione and phospholipids are lowered. Oxidative stress indices, ameliorated mitochondrial activities, and peroxided cardiolipin were drastically decreased in rats with diabetes treated with BCP or MET. Conclusions: The present research demonstrated that BCP improved the vital role of mitochondria by reducing free radical dominance in type 2 diabetic experimental rats fed high-fat and high-sugar diets.